0

1.1kviews

Simplify this equation & realize using basic gates

written 5.6 years ago by | • modified 3.4 years ago |

$ Y = ABC +B\overline{C}D + \overline{A}BC$

ADD COMMENT
EDIT

**1 Answer**

0

1.1kviews

Simplify this equation & realize using basic gates

written 5.6 years ago by | • modified 3.4 years ago |

$ Y = ABC +B\overline{C}D + \overline{A}BC$

ADD COMMENT
EDIT

0

4views

written 5.6 years ago by | • modified 5.6 years ago |

$Y =ABC + B\overline{C}D + \overline {A}BC $

$= BC + B\overline{C}D \hspace{2cm} since\hspace{.2cm} (A+\overline{A})=1 $

$= B(C+\overline{C}D) $

$=B(B+D) \hspace{2.2cm} since\hspace{.2cm}A+\overline{A}B=A+B $

Which is required expression the realization of this expression is as shown below

ADD COMMENT
EDIT

Please log in to add an answer.